Zur Entwicklung städtischer Siedlungen in Äthiopien - Kuls, Wolfgang (ERDKUNDE, 1970)
Ethiopia lacks a framework of older urban settlement adapted to present needs and circumstances. The towns of the present day have largely grown up since the turn of the century with the development of a modern State apparatus which necessitated the construction of secure seats of administration, permanent trade and supply centres. The contemporary situation is marked by the dominance which Addis Ababa and Asmara exert over all other urban settlements in size and importance, to such an extent that viable regional towns are absent in this fragmented country. The 'towns' found in the Provinces (called by the local name 'Katama' because of the frequent doubt as to the applicability of the term 'town') are, above all, well equipped with facilities in the tertiary sector while industry, apart from a few development regions, has played no role to date. This paper first explains the reasons for the lack of an urban culture in Ethiopia, then reviews the phases of development of urban settlement since the second half of the 19th century. A discussion of the distribution pattern follows and, in a second main section, the typical structural and functional characteristics of Katama-settlements are described.